Penanganan Acne Vulgaris Terkini - Yulinar Maulida; M. Mimbar Topik (Pusat Riset dan Inovasi Nasional, 2024)
Acne Vulgaris (AV) is a chronic inflammatory skin disorder in the pilosebaceous unit. This condition generally manifests as papules, pustules, or nodules especially on the face and can also affect the upper arms, trunk and back. AV is ideopathic, but can also be caused by increased sebum production, hyperkeratinization of hair follicles, colonies of Propionibacterium acnes (P. acnes) bacteria and inflammatory processes. Some of these causes are related to risk factors as triggers, such as food factors, use of cosmetics, and psychological stress. AV is one of the most common dermatological conditions worldwide with an estimated 650 million people affected by this disease. The study of the Global Burden of Disease (GBD) reports that AV attacks around 85% of young adults aged 12-25 years. Based on gender, women suffer more from AV than men with percentages of 69.7% and 30.3% respectively. Treatment of acne vulgaris is based on the level and severity of the acne. Treatment can be divided into pharmacological and physical therapy. Pharmacological therapy is the first line of treatment for acne vulgaris, it can be divided into topical and systemic treatment.